2021
DOI: 10.1136/bmjopen-2020-045353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tourniquet use on the risk of revision in total knee replacement surgery: an analysis of the National Joint Registry Data Set

Abstract: ObjectiveTourniquet use in total knee replacement (TKR) is believed to improve the bone-cement interface by reducing bleeding, potentially prolonging implant survival. This study aimed to compare the risk of revision for primary cemented TKR performed with or without a tourniquet.DesignWe analysed data from the National Joint Registry (NJR) for all primary cemented TKRs performed in England and Wales between April 2003 and December 2003. Kaplan-Meier plots and Cox regression were used to assess the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While improved cementation and implant fixation is one of the proposed benefits of tourniquet in primary TKA, this has been disputed in several studies using radiostereometric analysis that have found similar cemented fixation with and without a tourniquet [6,7]. This is supported by a large nationwide UK register study showing that the use of a tourniquet did not have any effect on prothesis survival [8].…”
mentioning
confidence: 99%
“…While improved cementation and implant fixation is one of the proposed benefits of tourniquet in primary TKA, this has been disputed in several studies using radiostereometric analysis that have found similar cemented fixation with and without a tourniquet [6,7]. This is supported by a large nationwide UK register study showing that the use of a tourniquet did not have any effect on prothesis survival [8].…”
mentioning
confidence: 99%